PERANCANGAN APLIKASI RENTAL MOBIL TRAVEL DESKTOP PADA PERUSAHAAN TIRTAYASA TRANS - Mochamad Yusuf Romdoni; Irma Yunita Ruhiawati; Waliadi Gunawan (Jurnal Sistem Informasi dan Informatika (Simika), 2022)
The purpose of this study is to analyze as well as provide input to a company, namely through the development of an information system that is currently used to process data for travel car rental services. Currently the computer application is one of the important factors for a company in managing all company activities to be more effective and easier. Even the use of technology through information systems has become the main requirement to show the quality of a field and become the most important capital in winning the competition. The information system for travel car rental services at Tirtayasa Trans needs to be designed because currently it is still using a separate data processing method in a spreadsheet application, where each daily or monthly transaction is grouped in each file so that this makes the filtering and reporting process difficult. The research method used in writing is a descriptive review method with a data collection technique approach, namely through observation, interviews, and literatur study. In addition, at the system development stage, the waterfall system is used. The design of this computer application can help companies to improve performance and car rental services in order to compete well in the world of travel car rental business.